The Effect of Electrode Moisture and Polarity On SMAW Welding of Low Carbon Steel - Hafni Hafni (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
Welding using moist electrodes and the choice of polarity is expected to affect the defects that usually arise in the welding results of ST 37 low carbon steel. To find out how big the influence of electrode humidity and polarity on defects in low carbon steel welding results, a study was carried out using fluid as an electrode moisturizing element. The electrode humidification process is carried out by allowing the electrodes to be contaminated by humidity for 3 days, 6 days and 9 days, before welding the base metal. After welding with these electrodes, metallographic testing is carried out to observe the macrostructure and microstructure of the welding results. From the test results, it is found that the humidity of the electrode does not affect the defects that arise in the welding results of low carbon steel as long as it does not damage the flux of the electrode.